IDENTIFIKASI TINGKAT KONSUMSI PANGAN MASYARAKAT DI KABUPATEII PELALAWAN - Ahmad Rifai; Gulat Medalie Mas Manurung (Universitas Riau, 2003)
The study aimed to identifivcation the household expenditure structure and food coasumption in Pelalawandistrict. The data used in the study was collected from survey In July to November 2(K)2. The result of studyshows that the avarage of houseliold income was Rp 803,135 per month, and the gini ratio of household incomewas 0.20. The household expenditure structure shows that the proportion of non-food expenditure is greaterthan the food expenditure. The consumption of rice and sugar was higer than the expected food consumption,wliile the consumption offish, meal, egg, vegetable and fruit was lower than the expected food coasumption.